Storage of Potassium Ions in Layered Vanadium Pentoxide Nanofiber Electrodes for Aqueous Pseudocapacitors. Issue 12 (7th October 2013) - Yeager, Matthew P.; Du, Wenxin; Bishop, Brendan; Sullivan, Matthew; Xu, Wenqian; Su, Dong; Senanayake, Sanjaya D.; Hanson, Jonathan; Teng, Xiaowei
<x xml:space="preserve">Abstract</x> Spaced out: This paper investigates potassium‐ion storage in vanadium pentoxide nanofibers (VNFs, K0.33V2O5) with a layered architecture. In situ XRD experiments reveal that the interplanar space of VNF expands/contracts upon extraction/insertion of potassium ions during the redox process.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>